Determination of 2,4-D and dicamba in food crops by MEKC - Lanças, F. M.; Rissato, S. R.; Galhiane, M. S. [UNESP] (Springer Nature, 1999)
The determination of 2,4-D (2,4-dichlorophenoxyacetic acid) and Dicamba (2-methoxy-3,6-dichlorobenzoic acid) residues in sugar cane, rice and corn was performed by a supercritical fluid extraction (SFE) method using CO2/acetone as extraction mix and an SFE apparatus developed in our laboratory. The extracts were cleaned up after extraction by both liquid- liquid partition and a Florisil column. Micellar electrokinetic capillary chromatography (MEKC) coupled with ultraviolet on-column detection was used for the analysis of these pesticides. The detection limits were improved by the preparation of a special detection cell with an increased pathlength that gave detection limits of ca. 0.6 pg for 2,4-D and Dicamba. Our results demonstrated that capillary electrophoresis can be a powerful new analytical tool for pesticide residue analysis.
Keywords: Dicamba and 2,4-D; Food Crops; Micellar Electrokinetic Chromatography; Supercritical Fluid Extraction; 2,4 dichlorophenoxyacetic acid; acetone; carbon dioxide; dicamba; magnesium trisilicate; pesticide; capillary electrophoresis; corn; crop; food; micellar electrokinetic chromatography; nonhuman; priority journal; rice; supercritical fluid extraction